2015
DOI: 10.1016/j.ejor.2014.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Price coordination in distribution channels: A dynamic perspective

Abstract: In this study, we investigate two important questions related to dynamic pricing in distribution channels: (i) Are coordinated pricing decisions efficient in a context where prices have carry-over effects on demand? (ii) Should firms practice a skimming or a penetration strategy if they choose to coordinate or to decentralize their activities? To answer these questions, we consider a differential game that takes place in a bilateral monopoly where the past retail prices paid by consumers contribute to the buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Zhang et al [20] formulated a differential equation in a bilateral monopoly market to study the pricing strategies in two distribution channels; they concluded that it is beneficial for the competitive supply chain to boost a higher initial Discrete Dynamics in Nature and Society 3 reference price. Benchekroun et al [5], Martín-Herrán et al (2012) [21], and Martín-Herrán and Taboubi (2015) [22] studied the reference price and the relative pricing strategies in the context of the supply chain. Most of the previous papers considered the reference price as an exponentially decaying weighted average of the past observed prices and neglected the operation factors which affect the reference price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang et al [20] formulated a differential equation in a bilateral monopoly market to study the pricing strategies in two distribution channels; they concluded that it is beneficial for the competitive supply chain to boost a higher initial Discrete Dynamics in Nature and Society 3 reference price. Benchekroun et al [5], Martín-Herrán et al (2012) [21], and Martín-Herrán and Taboubi (2015) [22] studied the reference price and the relative pricing strategies in the context of the supply chain. Most of the previous papers considered the reference price as an exponentially decaying weighted average of the past observed prices and neglected the operation factors which affect the reference price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Popescu and Wu [12] studied the dynamic pricing problem of a monopolist firm under a discrete time model; they showed that if consumers are loss averse, optimal prices will converge to a constant steadystate price, otherwise, optimal policy cycles. Martín-Herrán and Taboubi [13] investigated whether the results on the efficiency of price coordination in bilateral monopolies still hold when the reference price effect is taken into account. They showed that, for some values of the initial reference price, there is a time interval where channel decentralization performs better than coordination.…”
Section: Related Literaturementioning
confidence: 99%
“…The exponential smoothing model, stemming from the adaptive expectation model, is the most commonly used updated model for reference price (see [12,13,25,48]):…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They found the optimal wholesale price and retail price could always maximize the manufacturer's profit. Martín-Herrán and Taboubi (2015) investigated the pricing strategy of the dual-channel distribution in a dynamic approach. They found there is a time interval where a dual-channel distribution with an independent retailer performs better than a dual-channel distribution with retail channel controlled by a manufacturer.…”
mentioning
confidence: 99%